Penerapan Media Emometer dalam Mendukung Kesejahteraan Psikososial Lansia - Zahra Adinda Syalsabila; Fayla Fatima; Hanny Saleha Resyakilla; Aura Adinda Raisya; Shafwah Kamilia Rizky; Hafshah Al Anshariyah; Mulyati Mulyati; Uswatun Hasanah; Riswano Riswano (Eastasouth Institute, 2026)
The increasing elderly population in Indonesia has led to progressive psychosocial decline, particularly among older adults living in nursing homes who are vulnerable to social isolation and cognitive impairment. This community service program aimed to design and implement the educational game Emometer as an innovative psychosocial stimulation medium at Atmabrata Nursing Home. Using a Research and Development (R&D) approach with descriptive–evaluative methods, the intervention involved 26 older adults through stages of needs analysis, creative content development, and media application. Program effectiveness was evaluated across five dimensions using a Likert scale. The results indicate that Emometer was highly effective, achieving moderate to high scores across all dimensions, including emotional comfort (96.2%), psychological benefits (100%), and media comprehension (96.1%). These findings suggest that Emometer is a valid non-pharmacological intervention to enhance emotional well-being, stimulate fine motor skills, and promote social interaction among older adults.